Miniature fluidic devices for nanoparticle synthesis with biomedical applications - Hong, Liying (2017)
Nanoparticles exhibit very distinct characteristics from their bulk counterparts, therefore there is great interest in studying the properties of these nanomaterials for various applications such as biophotonics, photovoltaics, and nanomedicine. Miniature devices not only provide the conveniences of small physical footprints and system portability, but also serve as excellent platforms to give us insight into the molecular interactions at reduced length and volume scales, requiring less amount of sample and hastening the sample processing time. Therefore, the union of these two concepts is the motivation behind this thesis as miniaturization of reaction vessels can provide better control over the reaction conditions, enabling higher reproducibility and tighter size distributions. As a result, nanocrystals with superior qualities like high monodispersity and narrow emission linewidths can be easily reproduced with less chemical wastage.